Beyond risk and vulnerability: a commentary on "TB, staring, love and loneliness: Flavia's story". Issue 4 (2nd October 2018) - Müller, Alex
Abstract : This article comments on the photo essay "TB, Staring, Love and Loneliness: Flavia's Story" by Pieter du Plessis, Siv Tshefu and Flavia Nazier, published in the same issue. It contextualizes the essay and Flavia's story against the historical and contemporary relationship between medicine and gender diversity to emphasise the essay's argument about agency and resilience.